The anthropological nature of M. M. Bakhtin’s chronotope - Sirotkin, Yuri L. (Izvestiya of Saratov University. Philosophy. Psychology. Pedagogy, 2022)
Introduction. The relevance of the topic is substantiated and the purpose of the study is formulated. Theoretical analysis. An anthropological interpretation of M. M. Bakhtin’s chronotope is proposed. The unity of the chronotope is maintained by the dynamically nonequilibrium ratio of time and space. Chronotope expands the idea of an event and a place. The simultaneous presence of a person in a chronotope and a chronotope in a person is organic and inseparable. The peculiarity of a person’s perception of a space-time whole is determined by the ability to perceive an artistic image framed as a text. A person feels several chronotopes and lives in them simultaneously, but they also coexist in a person in parallel. The world of the heroes of the Renaissance narrative becomes open, while maintaining the integrity of the chronotope perception. The role of the road as a meeting place at the intersection of space-time perspectives is of exceptional importance. Conclusion. The anthropological nature of the chronotope is revealed. The concept of a chronotope is defined as a space-time whole. The formula of a person in a chronotope and a chronotope in a person is derived. The continuity of the chronotope is indicated by an event and a place. The perception of time-space has a concrete historical character and is carried out through the comprehension of an artistic image. In Modern times, the universalization of the perception of the chronotope is being consolidated, deepening the understanding of its anthropological nature.